Atom-efficient synthesis of a benchmark electrolyte for magnesium battery applications. Issue 86 (11th October 2022) - Brown, Scott A.; Cussen, Serena A.; Kennard, Rhiannon; Marchesini, Sofia; Pryke, Jethro J.; Rae, Annabel; Robertson, Stuart D.; Samajdar, Rudra N.; Wain, Andrew J.
Abstract : The Mg battery electrolyte complex [Mg2 Cl3 ] + [AlPh4 ] − is prepared in high yield with 100% atom economy via a AlCl3 /MgPh2 ligand exchange reaction. Spectroscopic studies suggest a simpler solution ionic composition than seen previously whilst maintaining high electrochemical performance. Abstract : The benchmark magnesium electrolyte, [Mg2 Cl3 ] + [AlPh4 ] −, can be prepared in a 100% atom-economic fashion by a ligand exchange reaction between AlCl3 and two molar equivalents of MgPh2 . NMR and vibrational spectroscopy indicate that the reported approach results in a simpler ionic composition than the more widely adopted synthesis route of combining PhMgCl with AlCl3 . Electrochemical performance has been validated by polarisation tests and cyclic voltammetry, which demonstrate excellent stability of electrolytes produced via this atom-efficient approach.